Work Engagementwith Organizational Citizenship Behavior (OCB) in Millennial Employees - Yosa Aunianova; Harri Kurniawan; Rina Mariana (Psyche 165 Journal, 2025)
The millennial generation is the most productive generation at work, for the next 10 years. However, the millennial generation has an individualistic nature that causes self-egocentricity, gets bored easily, and is impatient and not fully responsible for their work. Of course, this does not show the behavior of helping fellow workers. So it is necessary to increase the employee's sense of attachment to work so that they tend to display voluntary behavior. This research was conducted on millennial employees at agency X. This study aims to empirically determine whether there is a relationship between Work Engagement and Organizational Citizenship Behavior (OCB) in Millennial Employees at Agency The subject of this study used the Saturated Sampling technique where all populations were used as samples. The test results show that the validity coefficient on Organizational Citizenship Behavior ranges from 0.305 to 0.934 with a reliability coefficient of 0.976. While the validity coefficient of Work Engagement ranges from 0.552 to 0.949 with a reliability coefficient of 0.964. Based on data analysis, a correlation value of 0.418 with a significance level of 0.000 is obtained, which means the hypothesis is accepted. This shows that there is a very significant relationship between Work Engagement and Organizational Citizenship Behavior with a positive direction for millennial employees at agency X. The effective contribution of the work engagement variable to organizational citizenship behavior is 17%.